Regulatory elements in vectors containing the ctEF-1α first intron and double enhancers for an efficient recombinant protein expression system - Lee, Chi-Pin; Ko, Albert Min-Shan; Chiang, Shang-Lun; Lu, Chi-Yu; Tsai, Eing-Mei; Ko, Ying-Chin (Scientific reports, 2018)
To establish a stable and scalable transient protein production system, we modified the EF-1 first intron size and verified the order of two recombinant enhancers downstream of the SV40 polyA sequence. This new vector was named pHH-Gemini (pHH-GM1) and was used to express alpha kinase 1 ( ALPK1 ) and various other proteins, NLRP3, F-actin, Camodulin, PP2A, URAT1, Rab11a and myosin IIA. The results showed that, compared with six commercial plasmids, pHH-GM1 significantly enhanced His-HA-ALPK1 expression in a western blot analysis of transfected HEK293T cells. The expression of various other genes was also successful using the pHH-GM1 vector. In addition, we inserted turbo green florescence protein (tGFP) into the pHH-GM1 vector, and an improvement in fluorescence intensity was observed after transient transfection of HEK293T cells. For large-scale production, protein production was tested by standard supplementation with one volume of medium, and volumetric yields of 2 and 2.3 mg/L were achieved with pHH-GM1-ALPK1 in HEK293-F and CHO-S cells, respectively. We found that cell viability was more than 70% 11 days after cells were transfected with the pHH-GM1 vector. The pHH-GM1 vector with the ctEF-1α first intron and double enhancers, Simian virus 40 and Cytomegalovirus (SV40 and CMV) is an efficient CMV promoter-based gene expression system that can potentially be applied to study genes of interest and improve protein production.